The Influence of Digital Marketing and Product Design on Purchasing Decisions for Suseno Banana Chips Products - Theodora, Clara; Warganegara, Tri Lestira Putri (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
This study aims to determine the influence of digital marketing and product design on purchasing decisions for Suseno banana chips in Bandar Lampung. The background of this research is based on the increasing competition in the snack food industry, particularly in banana chip products. The research method used is quantitative. The data used are primary data obtained directly by the researcher through questionnaires involving 98 respondents, determined using the Slovin formula. The sample was taken using a non-probability sampling technique with a purposive sampling approach. The data analysis techniques include validity test, reliability test, normality test, multicollinearity test, multiple linear regression analysis, t-test, F-test, and coefficient of determination (R²). The results show that both digital marketing and product design have a significant influence on purchasing decisions, both partially and simultaneously. Digital marketing has a more dominant influence compared to product design. These findings highlight the importance of integrating relevant digital marketing strategies and product design to enhance competitiveness and drive consumer purchasing decisions.